Testing the Predictive Power of Dividend Yields - Goetzmann, William N.; Jorion, Philippe (Journal of Finance, 1993)
This paper reexamines the ability of dividend yields to predict long-horizon stock returns. The authors use the bootstrap methodology, as well as simulations, to examine the distribution of test statistics under the null hypothesis of no forecasting ability. These experiments are constructed so as to maintain the dynamics of regressions with lagged dependent variables over long horizons. They find that the empirically observed statistics are well within the 95 percent bounds of their simulated distributions. Overall there is no strong statistical evidence indicating that dividend yields can be used to forecast stock returns. Copyright 1993 by American Finance Association.(This abstract was borrowed from another version of this item.)(This abstract was borrowed from another version of this item.)